Simulation and Modeling Methodologies, Technologies and Applications International Conference, SIMULTECH 2012 Rome, Italy, July 28-31, 2012 Revised Selected Papers - Obaidat, Mohammad S.; Filipe, Joaquim; Kacprzyk, Janusz; Pina, Nuno (Advances in Intelligent Systems and Computing,, 2014)
This book includes extended and revised versions of a set of selected papers from the 2012 International Conference on Simulation and Modeling Methodologies, Technologies and Applications (SIMULTECH 2012) which was sponsored by the Institute for Systems and Technologies of Information, Control and Communication (INSTICC) and held in Rome, Italy. SIMULTECH 2012 was technically co-sponsored by the Society for Modeling & Simulation International (SCS), GDR I3, Lionphant Simulation, Simulation Team and IFIP and held in cooperation with AIS Special Interest Group of Modeling and Simulation (AIS SIGMAS) and the Movimento Italiano Modellazione e Simulazione (MIMOS).